2010
DOI: 10.1016/j.cnsns.2009.11.016
|View full text |Cite
|
Sign up to set email alerts
|

A note on solitary travelling-wave solutions to the transformed reduced Ostrovsky equation

Abstract: Two recent papers are considered in which solitary travelling-wave solutions to the transformed reduced Ostrovsky equation are presented. It is shown that these solutions are disguised versions of previously known solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Unfortunately the author [1] does not suggest new results to the problem of integrability of systems (1) except trivial exercise on the application of the Hirota method to the Korteveg-de Vries equation. He has made the continuation of the errors that were discussed in papers [8][9][10][11][12][13][14][15].…”
Section: Commun Nonlinear Sci Numer Simulat J O U R N a L H O M E P Amentioning
confidence: 98%
“…Unfortunately the author [1] does not suggest new results to the problem of integrability of systems (1) except trivial exercise on the application of the Hirota method to the Korteveg-de Vries equation. He has made the continuation of the errors that were discussed in papers [8][9][10][11][12][13][14][15].…”
Section: Commun Nonlinear Sci Numer Simulat J O U R N a L H O M E P Amentioning
confidence: 98%
“…One should always study a problem in eagle-eyed solving mode, and check the results with the computer interactively. Recently, Parkes [6][7][8] and Kudryashov [9][10][11][12][13] have been continuously alerting the authors for equivalent, disguised, and incorrect results. Unfortunately, a number of cases have appeared in the literature when solutions derived by the basic Exp-function method are irrelevant [14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…The foregoing illustrative discussion exemplifies two deficiencies of the ( ′ / )-expansion method: firstly, that the method delivers solutions in a cumbersome form (see (11) with (12), or (13), for example) and secondly, that the solutions appear to contain more free parameters than is actually the case. Typically, each solution can be manipulated into a neater form which displays the correct number of free parameters.…”
mentioning
confidence: 99%
“…Twenty eight solutions were derived including 'many new' solutions. However, in [11] we showed that all twenty eight solutions may be reduced to 11 or 12 . In [13], the solutions 11 , 21 and 3 were derived via a method involving Laurent series.…”
mentioning
confidence: 99%
See 1 more Smart Citation